A New Mutation Causing Severe Infantile-Onset Pompe Disease Responsive to Enzyme Replacement Therapy - Hossein Moravej; Anis Amirhakimi; Alireza Showraki; Hamid Amoozgar; Zahra Hadipour; Ghasem Nikfar (Iranian Journal of Medical Sciences, 2018)
Pompe disease (PD), also known as “glycogen storage disease type II (OMIM # 232300)” is a rare autosomal recessive disorder characterized by progressive glycogen accumulation in cellular lysosomes. It ultimately leads to cellular damage. Infantile-onset Pompe disease (IOPD) is the most severe type of this disease and is characterized by severe hypertrophic cardiomyopathy and generalized hypotonia. Mutations in the acid alpha-glucosidase (GAA) gene, located at locus 17q25.3, are responsible for the disease leading to reduced activity of the acid alpha-glucosidase enzyme. To date, approximately 400 pathogenic mutations have been reported in the GAA gene. The aim of this study is to report a novel nonsense mutation in exon 4 of the GAA gene in an Iranian child suffering from IOPD. The patient was a female neonate with hypertrophic cardiomyopathy and a positive family history of IOPD. After definite diagnosis, enzyme-replacement therapy (ERT) was started for the patient, who was 2 months old. Now at the age of 20 months, she has had good growth and development and her echocardiographic parameters are within the normal range. This report shows that IOPD patients with this mutation can be treated with ERT successfully.